Diseño geométrico y estructural de la vía Guayacán - Los Ríos, ubicado en el cantón El Guabo - provincia de El Oro. - Toro Aguilar, José Luis (2015)
This project has to do with "GEOMETRIC STRUCTURAL DESIGN AND ROUTE GUAYACAN-LOS RIOS; LOCATED IN El Guabo Canton - PROVINCE OF GOLD ". With a length of 8km, the project is to study the current situation and design a road system so as to allow the people of Guayacán and Rivers improve their quality of life. In addition, the project should consider the following: Facilitate the transportation sectors between the way Guayacán -The Rivers, which is an agricultural and livestock mostly site. Improve transport and trade of various agricultural products and livestock in existing mentioned sector. integrated development of areas adjacent to the sector under study. There is a proper road communication between the peoples of Guayacán and Los Rios and be the life of the inhabitants much better. Promote tourism for both sectors Project implementation will allow easy access both vehicles and people to different sectors located in this way, activating the social and commercial activities. With the delivery of work titling beneficiaries they are: Decentralized Autonomous Provincial Government of El Oro and consequently the residents. Counting using the vestry of Rio Bonito represented by Francisco de la Cruz Ramirez Ortega, and the support of the Autonomous Decentralized Provincial Government of El Oro, giving us such public institutions documents and information necessary to carry out this work titling.